Carbonate contents in sediments collected at Four-Way Closure Ridge, RV Sonne cruise SO266/1, South China Sea - Bohrmann, Gerhard (PANGAEA, 2022)
During cruise SO266/1 deep sediment cores were collected using MARUM-MeBo200 from Formosa Ridge and Four-Way Closure Ridge, South China Sea. Near-surface sediments were retrieved from same positions by use of a gravity corer. Sediment was sampled from selected core depths. Carbonate (CaCO3) contents of bulk sediment samples were determined by high-temperature combustion and subsequent analysis of CO2 contents with a Vario EL III (Elementar Analysensysteme GmbH) elemental analyzer. Data pairs indicated are single measurements for sediments samples from individual cores.